Wokół Rot kościańskich. O specyficznej sytuacji edytorskiej - Borowiec, Karolina (My University, 2013)
The article focuses on one of the unnoticed lexical replacements, derived from the fifteenth-century Polish rota’s judicial oaths, written in Kościan (Wielkopolska). The case of this short notes remains unprecedented in the history of Old Polish language – about 370 sentences survives in two wordings: draft and fair copy; partially written and re-written by the same hand. Comparing equivalents from drafts and fair copies, author shows that problem have not been sufficiently recognized and explored probably because of the last edition of these texts, devoid of transcription and containing some errors (results of the research method). Author proves, that the draft notation nadwÿſlane, published in Wielkopolskie roty sądowe XIV-XV w. as nad wysłanie should be rather read out as nadwiślane, according to lexical equivalent (nad wÿſlowe – nadwisłowe) which appears in fair copy, written by the hand of another writer. New edition, necessary to further researches, and further studies could lead us to discover the nature of replacements introduced in fair copies and make us able to follow the writing process in medieval Polish court.
Around the rota’s judicial oaths from Kościan. About the specific editorial situation
Keywords: roty kościańskie; brudnopisy i czystopisy; średniowieczne roty sądowe; drafts and fair copies; medieval court